Analisis Kebijakan Pemerintah Dalam Peningkatan Kualitas Pembangunan Manusia: Studi Pada Seluruh Provinsi di Pulau Jawa - Julian, Isman; Nurul Anwar; Barokatuminalloh (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The Human Development Index (HDI) is one of the indicators to measure community welfare and an overview of the success of the implementation of a region's development policy. The success of a region is inseparable from the role of the central and regional governments. So it is necessary to make several efforts and strategies that can increase the human development index. This study aims to analyze government policies in improving the quality of human development throughout Java Province. This study uses quantitative panel data using PVAR and PVECM analysis methods. The data used is secondary data in the form of human development index, government expenditure in the education sector, government expenditure in the health sector, unemployment and economic growth from 2011-2020. The results of the analysis show that there is a one-way causal relationship between government expenditure in the health sector and HDI and has long-term and short-term effects. There is a two-way causal relationship between economic growth and HDI and has long-term and short-term effects.